The Relationship Between Severity Level And Quality Of Worship Among Muslim Patients Undergoing Hemodialysis At PKU Muhammadiyah Hospital, Gamping - Siti Nurhaliza; Ruhyana Ruhyana; Aini Inayati (CV. AFDIFAL MAJU BERKAH, 2026)
The quality of worship is related to the level of devotion and spiritual appreciation in daily life. Chronic kidney failure is a condition that progressively affects kidney function and requires hemodialysis as replacement therapy. This condition can affect the ability of Muslim patients to perform their daily worship. Although spiritual aspects are important in health care, research on the relationship between disease severity and quality of worship in hemodialysis patients is still limited, especially in Indonesia. This study aims to analyze the relationship between disease severity and the quality of worship among Muslim patients undergoing hemodialysis at PKU Muhammadiyah Gamping General Hospital. This study used a descriptive correlational method with a cross-sectional approach. A total of 62 respondents were selected using random sampling. Data were collected using a research instrument that had been tested by three experts. Data analysis was performed using Spearman's rank correlation. The results showed that there was no significant relationship between disease severity and the quality of worship among Muslim patients undergoing hemodialysis (r = 0.174; p = 0.175). This study indicates that disease severity does not affect the quality of worship among hemodialysis patients, meaning that patients can maintain their worship practices despite experiencing severe illness.